Engaging patients in designing a transmural allied health pathway: A qualitative exploration of hospital‐to‐home transitions - Juul W. M. vanGrootel; Romain J. Collet; Mel E. Major; Suzanne Wiertsema; Hanneke vanDongen; Marike van derLeeden; Edwin Geleijn; Raymond Ostelo; Marike van derSchaaf (Wiley, 2024)
Abstract Introduction The transition from hospital to home is often suboptimal, resulting in patients not receiving the necessary allied healthcare after discharge. This may, in turn, lead to delayed recovery, a higher number of readmissions, more emergency department visits and an increase in mortality and healthcare costs. This study aimed to gain insight into patients' experiences, perceptions, and needs regarding hospital‐to‐home transition, focusing on allied healthcare as a first step towards the development of a transitional integrated allied healthcare pathway for patients with complex care needs after hospital discharge. Methods We conducted semistructured interviews with patients. Participants were recruited from universities and general hospitals in the Amsterdam region between May and July 2023. They were eligible if they (1) were discharged from the hospital minimally 3 and maximally 12 months after admission to an oncologic surgery department, internal medicine department, intensive care unit, or trauma centre, (2) received hospital‐based care from at least one allied healthcare provider, who visited the patient at least twice during hospital admission, (3) spoke Dutch or English and (4) were 18 years or older. Interviews were audio‐recorded and transcribed verbatim. We performed a thematic analysis of the interview data. Results Nineteen patients were interviewed. Three themes emerged from the analysis. 'Allied healthcare support during transition' depicts patients' positive experiences when they felt supported by allied health professionals during the hospital‐to‐home transition. 'Patient and family involvement' illustrates how much patients value the involvement of their family members during discharge planning. 'Information recall and processing' portrays the challenges of understanding and remembering overwhelming amounts of information, sometimes unclear and provided at the wrong moment. Overall, patients' experiences of transitional care were positive when they were involved in the discharge process. Negative experiences occurred when their preferences for postdischarge communication were ignored. Conclusions This study suggests that allied health professionals need to continuously collaborate and communicate with each other to provide patients and their families with the personalized support they need. To provide high‐quality and person‐centred care, it is essential to consider how, when, and what information to provide to patients and their families to allow them to contribute to their recovery actively. Patient or Public Contribution The interview guide for this manuscript was developed with the assistance of patients, who reviewed it and provided us with feedback. Furthermore, patients provided us with their valuable lived experiences by participating in the interviews conducted for this study.